1997
DOI: 10.1136/bmj.315.7106.464
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal of long term diuretic medication in elderly patients: a double blind randomised trial

Abstract: Objectives: About 20% of elderly people use long term diuretic medication, but there is doubt whether prolonged diuretic medication on such a large scale is necessary. We performed a study to assess what proportion may successfully be withdrawn from diuretic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
2
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(53 citation statements)
references
References 15 publications
1
46
2
4
Order By: Relevance
“…9,10 In contrast to the findings of Walma et al, 13 only a few of the patients in the present study restarted medication because of oedema; most restarted because of raised blood pressure.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 54%
See 2 more Smart Citations
“…9,10 In contrast to the findings of Walma et al, 13 only a few of the patients in the present study restarted medication because of oedema; most restarted because of raised blood pressure.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 54%
“…This is similar to the findings of Espeland et al, but lower than the 55% restarting patients reported by Aylett et al 9 Patients in the present study who used more than two cardiovascular drugs before stopping medication were more likely to restart medication within 6 months, which is in line with the review study of Nelson et al 14 However, these three latter studies concerned withdrawal from antihypertensive medication in normotensive patients, 9,13,14 whereas the present study re-evaluated the need for medication in both normotensive and (presumed) hypertensive patients.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 35%
See 1 more Smart Citation
“…Unfortunately, it is unclear whether such an approach is safe. Withdrawal of antihypertensives in older persons (not specifically in the context of frailty or polypharmacy) generally has been associated with a return of hypertension without an increase in the incidence of cardiovascular disease, [89][90][91][92][93] but these studies used liberal rules for reinitiating antihypertensives and were thus underpowered. Withdrawal of diuretics has been shown to be associated with an increased risk of developing heart failure, especially in the first 4 weeks after withdrawal, 92 and withdrawal of diuretics should therefore be accompanied by strict monitoring.…”
Section: Antihypertensive Drug Treatment In the Oldest Oldmentioning
confidence: 99%
“…Thirdly, we did not use either beta blockers or spironolactone; thus, the results may not apply to patients treated with these drugs. Finally, the follow-up period was short although it has been demonstrated that reinstitution of diuretics generally occurs in the early weeks after discontinuation [13]. In addition, it has to be emphasized that our results are probably not applicable to more severe heart failure patients, those that are receiving more elevated doses of loop diuretics or those with advanced heart failure (New York Heart Association classes III or IV).…”
Section: Study Limitationsmentioning
confidence: 86%